Stimulus Preference Assessment Methods for Identifying Reinforcers (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Learning and maintenance of behavioral repertories greatly depends upon consequences produced by such behaviors. Identifying consequences that increase the probability of social significant behavior is fundamental for behavioral interventions. Stimulus Preference Assessment (SPA) methods aims to identify preferred items that can be used as consequences. Eight SPA methods are described, two indirect: interview with parents and caregivers and informal observations; and six direct methods, which involve the presentation of single item; paired stimulus; multiple stimulus with and without replacement; and free operant in natural and restricted environment. Guidance on the stimulus choice, prerequisites, evaluation procedure, data recording and analysis, advantages and disadvantages are provided for each method.
Keywords: Preference assessment; reinforcement; choice